2022
DOI: 10.3390/ijms232113313
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathologic Role of Eosinophils in Eosinophilic Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a diverse chronic inflammatory disease of the sinonasal mucosa. CRS manifests itself in a variety of clinical and immunologic patterns. The histological hallmark of eosinophilic CRS (ECRS) is eosinophil infiltration. ECRS is associated with severe disease severity, increased comorbidity, and a higher recurrence rate, as well as thick mucus production. Eosinophils play an important role in these ECRS clinical characteristics. Eosinophils are multipotential effector cells that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Various mechanisms have been identified by researchers to explain the occurrence of eosinophilic infiltration in CRSwNP (57,58). It is evident that in CRSwNP, there is an accumulation of Charcot-Leyden Crystals (CLCs) within the tissues, as indicated by previous research (42).…”
Section: Role Of Eosinophils In Crswnpmentioning
confidence: 84%
See 1 more Smart Citation
“…Various mechanisms have been identified by researchers to explain the occurrence of eosinophilic infiltration in CRSwNP (57,58). It is evident that in CRSwNP, there is an accumulation of Charcot-Leyden Crystals (CLCs) within the tissues, as indicated by previous research (42).…”
Section: Role Of Eosinophils In Crswnpmentioning
confidence: 84%
“…This effect is mirrored in the lungs of asthmatic patients who exhibit increased levels of TSLP compared to healthy individuals (110). After exposure to allergens, IL-25 is markedly upregulated in the bronchial mucosa and nasal polyps of CRSwNP patients (57,111). Elevated levels of IL-25 in nasal polyps are also indicative of a positive response to corticosteroid treatment (112).…”
Section: Cellular Interactions In Eosinophilic Asthmamentioning
confidence: 97%
“…The activated Th2 cells and ILC2s recruit and activate basophils, mast cells and eosinophils by secreting IL-4, IL-5, and IL-13 [21,22]. IL-5 induces the maturation of eosinophils and the release of toxic granules to cause tissue damage and inflammation, leading to tissue remodeling and exacerbating nasal pathology [23,24]. Several studies have demonstrated that intravenous administration of a humanized anti-human IL-5 monoclonal antibody reduced the size of nasal polyps [25,26].…”
Section: Excessive Type 2 Inflammatory Response In Ar and Crswnpmentioning
confidence: 99%
“…The clinical suspect of AR firstly relies on symptoms, including one or more of the following symptoms, such as pruritus, sneezing, rhinorrhoea, nasal congestion, and hyposmia that arise within minutes after the exposition to allergen until 1-2 hours; late symptoms are nasal obstruction, hyposmia, nasal hyper reactivity and post nasal mucous discharge. [46][47][48] Allergic rhinitis can be perennial or seasonal, according to the relevant allergen, but this classification is not applicable globally, so the Allergic Rhinitis and its Impact on Asthma (ARIA) group has classified AR into intermittent or persistent on the duration of symptoms. 22 The clinical history is essential for diagnosing and profiling rhinitis in children in order to provide the most appropriate treatment and to establish the best management for the patient.…”
Section: Diagnostic Work-up and Differential Diagnosismentioning
confidence: 99%